Evolution of Sociology. Future and history - Castro H., Pablo de Jesús (Revista de Museología "Kóot", 2017)
This synthesis aims to describe very general elements on its historical origins, evolution and future projection. There are three main entries: the arise of the intellectual elites on which the classical social sciences-sociology arose, leaving a heritage to the contemporary generations 2- the creation of its object of study based on a system of concepts and categories that build theories, methods, and social as well as academic practices. 3- to pinpoint innovative processes of scientific research which produce a sociological knowledge and thought therefore qualifying is status as a social science open to the needs and realities of this present-future.